Energy-saving evaluation of a solar integrated vacuum freeze-dryer and building air conditioning system. Issue 2 (March 2021) - Zhou, Zhongwei; Guo, Yun; Lin, Yaolin
Vacuum freeze-dryer has been widely used in many fields such as food, medicine, and beverage. In the actual operation process, the freeze-dryer and factory buildings need to consume a lot of cold energy. In order to reduce energy consumption, this paper presents a freeze-dryer system using solar energy absorption refrigeration in conjunction with buildings. Through the solar absorption refrigeration system, the cooling capacity is supplied to the freeze-dryer and the building at the same time, so that the cold can be cascaded utilization. The simulation of the system by TRNSYS software shows that the system can greatly reduce the consumption of conventional energy, and it is a new energy-saving measure of vacuum freeze-dryer and building air conditioning.